2019
DOI: 10.2147/dddt.s180842
|View full text |Cite
|
Sign up to set email alerts
|

<p>Drug-release system of microchannel transport used in minimally invasive surgery for hemostasis</p>

Abstract: BackgroundSucrose allyl ether (SAE) containing hemostatic drugs and a photoinitiator was established to treat mild postpartum hemorrhage or long-term continuous abnormal uterine bleeding in minimally invasive surgery (MIS) using a photopolymerization method.Methods and resultsReal-time infrared spectroscopy and rheological experiments showed that the SAE monomer with shear-thinning characteristics could polymerize rapidly into a transparent membrane. Cytotoxicity experiments in vitro showed that this system co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our quantum chemistry calculation showed (Figure S1) that when a benzoyl radical from photocleavage of HMPP is added onto the double bond of AME, the addition rate constant ( k ) in the gas state is 4.6 × 10 –21 , one thousand times slower than k for addition to acrylate (2.2 × 10 –18 ) . However, in a previous study, we observed that SAE polymerization proceeded at a fairly rapid rate and formed a stable polymer, a phenomenon that is difficult to explain using the traditional FRA polymerization mechanism.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Our quantum chemistry calculation showed (Figure S1) that when a benzoyl radical from photocleavage of HMPP is added onto the double bond of AME, the addition rate constant ( k ) in the gas state is 4.6 × 10 –21 , one thousand times slower than k for addition to acrylate (2.2 × 10 –18 ) . However, in a previous study, we observed that SAE polymerization proceeded at a fairly rapid rate and formed a stable polymer, a phenomenon that is difficult to explain using the traditional FRA polymerization mechanism.…”
Section: Resultsmentioning
confidence: 82%
“…Bulter and Angelo asserted that the most important chain propagation pathway in diene polymerization is cyclization with cyclolinear polymer products. However, in our experience, polymeric products with high molecular weights were also obtained easily. , A noticeable monomer, sucrose allyl ether (SAE), was polymerized at room temperature using ultraviolet light, and the product (poly-SAE) was successfully applied in minimally invasive surgery as a hemostatic material.…”
Section: Introductionmentioning
confidence: 99%
“…This integration scheme has successfully been employed to address non-covalent binding energy in a ligand-target study. 35 Here, we used this approach at the quantum mechanical level of theory to assess the π-stacking between the oxindole and phenyl moieties along the reaction path. The electron sharing score (Δ𝑔 !…”
Section: Computational Detailsmentioning
confidence: 99%